PHYSIOLOGY AND PSYCHOLOGY OF BRAIN DEVELOPMENT IN EARLY CHILDHOOD (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article examines the physiology and psychology of brain development in early childhood based on a qualitative literature review of peer-reviewed scientific studies. The early years of life represent a critical period for neural growth, synaptic formation, and cognitive maturation. The study analyzes biological processes such as neurogenesis, synaptic plasticity, and myelination and their relationship with psychological functions including memory, attention, emotional regulation, and social behavior. Data were collected from major scientific databases, and key findings indicate that early environmental stimulation significantly shapes brain architecture and long-term psychological outcomes. Understanding the interaction between physiological mechanisms and psychological development is essential for improving early childhood education strategies and supporting healthy cognitive growth.
Keywords: Early Childhood – The developmental period from birth to around six years marked by rapid brain growth and high neural plasticity.